Left-Sided Portal Hypertension: A Sinister Entity - Fernandes,Alexandra (2015)
Introduction: Sinistral, or left-sided, portal hypertension (SPH) is a rare entity, with multiple potential causes. Gastrointestinal variceal bleeding and hypersplenism are its major clinical manifestations. The main aim of the present study is to summarize the clinical features ofpatients with SPH. Patients and methods: This was a retrospective analysis of consecutive patients with present or previous diagnosis of SHP, observed in a Gastroenterology Department, in a period of 2 years. Patients with clinical, radiological or laboratory alterations suggestive of cirrhosis were excluded. Causes of SPH, clinical manifestations and outcomes were registered. Potential factors associated with gastrointestinal bleeding were analyzed. Results: In the study period a total of 22 patients (male - 17; mean age - 9.6±10.6 years) with SHP were included. Clinical manifestations were: asymptomatic/unspecific abdominal pain (n = 14); gastrointestinal bleeding (n = 8). Eleven (50%) patients had increased aminotransferases, GGT and/or alkaline phosphatase although liver function was normal in all of them. Causes of SPH were chronic pancreatitis (n = 7), acute pancreatitis (n = 7), pancreatic cancer (n = 4), pancreatic surgery (n = 3) and arteriovenous malformation (n = 1). All patients had gastric and/or esophageal varices and seven had splenomegaly. Five (22.7%) had thrombocytopenia, associated with hypersplenism. Five patients (22.7%) were submitted to endoscopic treatment and eight were submitted to splenic artery embolization and/or splenectomy. There were no cases of variceal rebleeding and two patients died. Patients without liver enzymes elevation had a higher probability of gastrointestinal bleeding (87.5% vs. 28.6%; p = 0.024). Conclusions: Acute and chronic pancreatitis are the major causes of SHP. Gastrointestinal bleeding is the most important clinical manifestation and patients without liver enzyme elevation seem more prone to bleed. Specific treatment is seldom performed or needed.